Quality assessment and anti-obesity activity of Stellaria media (Linn.) Vill - Rani Neerja; Vasudeva Neeru; Sharma Surendra (BMC, 2012)
Abstract Background Obesity is recognized as a social problem, associated with serious health risks and increased mortality. Numerous trials have been conducted to find and develop new anti-obesity drugs through herbal sources to minimize side effects associated with the present anti-obesity drugs. The present study was designed to evaluate the quality control parameters, quantitative phytochemical analysis (total phenolic, total flavonoids and total saponin content), and the anti-obesity effect of lyophilized juice (LJ) of Stellaria media (Linn.) Vill. by employing in vitro and in vivo models. Methods In vitro studies were performed to evaluate the inhibitory activity of LJ on pancreatic amylase and lipase. The in vivo pancreatic lipase activity was evaluated by measurement of plasma triacylglycerol levels after oral administration of lipid emulsion to swiss albino mice. Furthermore, the anti-obesity effect of LJ was assessed at two doses, 400 mg/kg and 900 mg/kg body weight in mice fed a high-fat-diet with or without LJ for 6 weeks. Results The LJ inhibited pancreatic amylase and lipase activity in vitro and elevated plasma triacylglycerol level in mice. LJ suppressed the increase in body weight, retroperitoneal adipose tissue, liver weights and serum parameters viz., total cholesterol, total triglyceride, LDL-cholesterol level at the dose of 900 mg/kg body weight of the mice fed with high fat diet. The total phenolic, flavonoid and saponin contents were found to be 0.26 mg/g, 1.4 mg/g and 1.19 μg/g respectively of LJ. Conclusion The anti-obesity effects of LJ in high-fat-diet fed mice may be partly mediated through delaying the intestinal absorption of dietary fat and carbohydrate by inhibiting digestive enzymes.